2020
DOI: 10.2217/nnm-2019-0316
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles as Contrast Agents for The Diagnosis of Alzheimer’s Disease: A Systematic Review

Abstract: Nanoparticle (NP)-based magnetic contrast agents have opened the potential for MRI to be used for early diagnosis of Alzheimer’s disease (AD). This article aims to review the current progress of research in this field. A comprehensive literature search was performed based on PubMed, Medline, EMBASE, PsychINFO and Scopus databases using the following terms: ‘Alzheimer’s disease’ AND ‘nanoparticles’ AND ‘Magnetic Resonance Imaging.’ 33 studies were included that described the development and utility of various N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 125 publications
0
17
0
Order By: Relevance
“…Of the techniques mentioned above, PET and MRI have been the primary imaging modalities used in AD, which allow the assessment of cortical atrophy and amyloid load, respectively. Additionally, glucose metabolism has been measured using fluorodeoxyglucose-PET [125].…”
Section: In Vivo Imaging Detection Platforms Of Ad Using Plasmonic Namentioning
confidence: 99%
See 2 more Smart Citations
“…Of the techniques mentioned above, PET and MRI have been the primary imaging modalities used in AD, which allow the assessment of cortical atrophy and amyloid load, respectively. Additionally, glucose metabolism has been measured using fluorodeoxyglucose-PET [125].…”
Section: In Vivo Imaging Detection Platforms Of Ad Using Plasmonic Namentioning
confidence: 99%
“…For successful identification and imaging of plaques in AD, NPs-contrast agents must be able to cross the blood-brain barrier (BBB) [127]. Furthermore, these agents should maintain colloidal stability, safely interact with organs and display effective renal or hepatic clearance to prevent accumulation and toxic effects [125].…”
Section: In Vivo Imaging Detection Platforms Of Ad Using Plasmonic Namentioning
confidence: 99%
See 1 more Smart Citation
“…It is indicated that nanoparticles could be used as drug delivery tools for the treatment of neurological diseases. [10][11][12] However, the detection limit of ELISA is only 0.312 ng mL −1 (Aβ) and 0.15 ng mL −1 (Tau), which prevents its clinical application. Therefore, the development of an ultra-sensitive detection technology for Aβamyloid and Tau protein is urgently needed for the early diagnosis of AD.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of nanoscale drug carriers such as liposomes, polymeric nanoparticles (NPs), inorganic NPs and bio‐NPs that are designed to deliver drugs more efficiently for AD diagnosis and therapy, have been covered by previous reviews (Agrawal et al, 2017; Mukherjee et al, 2020; Rodriguez‐Otormin et al, 2019; Ulanova et al, 2020). However, these nanocarriers usually target a specific pathological factor and are insufficient to overcome the complex pathological environment of AD.…”
Section: Introductionmentioning
confidence: 99%